The Effect Of Differentiated Learning On Students' Mathematical Self-Efficacy On The Probability Material In Grade X - Sianturi, Krismawati; Hutauruk, Agusmanto J. B; Sihombing, Dame Ifa (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to determine the effect of differentiated learning on students' mathematical self-efficacy in probability material in class X of SMK Negeri 5 Medan in the 2024/2025 academic year. The type of research is a quasi-experiment with sampling using the Cluster Random Sampling technique. The researcher used a questionnaire and observation as instruments to collect data. The results of the data analysis showed that the sig value (2-tailed) was 0.000 <0.05 at a significance level of 5%, which means that there is an effect of differentiated learning on students' mathematical self-efficacy in probability material in class X of SMK Negeri 5 Medan. From the results obtained the regression equation Ŷ = 17.615 + 0.431 ???? . Based on the results of the regression significance test, it can be concluded that there is an influence between differentiated learning on students' mathematical self-efficacy. The magnitude of the influence calculated with the coefficient of determination ( ???? 2) is 61.2%, meaning it is included in the moderate category and the relationship between differentiated learning and students' mathematical Self-efficacy with a value of r = 0.782, which means that both variables have a relationship with the percentage of values in the moderate category.